Is the behavioral component in the Family Assessment Device uni‐ or multidimensional?. Issue 3 (3rd December 2019) - Tan, Jason H. P.; Tsamparli, Anastasia; Adamis, Dimitrios
Abstract: The Family Assessment Device is a tool that helps to see the extent of family functioning, and there have been many published articles concerning its psychometric properties. However, the Behavior Control subscale has shown consistent low Cronbach's α scores which suggests that this component may be multidimensional in construct.